Egophoricity - Floyd, Simeon; Norcliffe, Elisabeth; San Roque, Lila (Typological studies in language, 2018)
Egophoricity is the grammaticalised encoding of personal knowledge or involvement. Markers in egophoric systems are sensitive to epistemic authority; since speakers generally know most about their own affairs, egophoric marking typically associates with first person statements. However, in questions epistemic authority shifts to the addressee, and egophoric markers associate with second person. This person sensitive distribution is found with subtle variations in unrelated languages around the globe. An under-studied and controversial category, egophoricity has been previously described under a wide range of labels linked to specific regional traditions. This is the first volume to consolidate these traditions into a global typology, including contributions from regions as diverse as the Himalayas, Western China, Highlands New Guinea, and the Andes. The volume further reveals how egophoric marking relates to conceptions of 'self' and 'other', giving special insights into notions of intentionality and the opacity of other minds across languages and cultures.